Caracterização de filme biodegradável a base de zeína e ácido oléico adicionado de nanocarbonato - Ribeiro, Wanessa Ximenes [UNESP]; Lopes Filho, José Francisco [UNESP]; Cortes, Monica Souza [UNESP] (FapUNIFESP (SciELO), 2015)
Zein oleic acid films added with 1, 2 and 3% (w/w) of nanocarbonate and 30% glycerol as plasticizer, were produced and evaluated according to their structure and functional properties. Structural characteristics were analyzed by optical and scanning electron microscopy (SEM). Water solubility and mechanical properties were determined according to ASTM methods. The increase of nanocarbonate concentration increased water solubility and influenced the color and mechanical properties. Optical and SEM of film samples added with nanocarbonate, shown low amount of pores and great fat globules size.
Characterization of biodegradable film based on zein and oleic acid added with nanocarbonate
Keywords: Biodegradable packaging; Nanocarbonate; Zein